Evaluation of Circulatory Concentration of Cytokines Platelet Derived Growth Factor-BB, Transforming Growth Factor Beta-1, and IL-10 in Canine Generalized Demodicosis - Parwari,; Mandali, GC; Parmar, Jignasha M; Mathakiya, RA (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The purpose of this study was to investigate the changes in circulating concentrations of PDGF-BB, TGF-β1 and interleukin-10 (IL-10) in  dogs with generalized demodicosis. Twelve dogs with generalized demodicosis were diagnosed based on clinical findings and microscopic  examination of the cutaneous scrapings. Six healthy dogs were included in the study as a control. Commercial specific ELISA assays  were used to measure circulating concentrations of plasma PDGF-BB, and serum TGF-β1 and IL-10. Marked and significant increase in  plasma PDGF-BB and serum TGF-β1 concentrations was evidenced in diseased dogs, while increase in serum IL-10 concentration was  non-significant. The levels of all three markers dropped down to near normal/healthy status after the treatment of diseased dogs. These  results indicate that the increased concentrations of circulating PDGF-BB, TGF-β1, and IL-10 play a pivotal role in the pathogenesis of  the canine demodicosis.
Keywords: Dog; ELISA assay; Generalized demodicosis; IL-10; PDGF-BB; TGF-β1; Immunosuppression